1970
DOI: 10.1111/j.1752-7325.1970.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Health of Narcotic Addicts

Abstract: This group of the School of Dentistry of the University of Maryland has a fortuitous opportunity to study a group of narcotic addicts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The mean OHI-S Index score was 2.70 in substance abusers which is comparable to the other studies by Angelillo et al [12], Shapiro et al, [13], Silverstein [14], Rosenstein [15], and Zahrani [16] who reported mean OHI-S values of 1.71, 2.67, 2.61, 2.2, and 2.42, respectively. The mean OHI-S score was significantly higher in the study group than the control group ( P = 0.001) especially among the male groups between the age groups of <20, 20–29, and 30–39 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean OHI-S Index score was 2.70 in substance abusers which is comparable to the other studies by Angelillo et al [12], Shapiro et al, [13], Silverstein [14], Rosenstein [15], and Zahrani [16] who reported mean OHI-S values of 1.71, 2.67, 2.61, 2.2, and 2.42, respectively. The mean OHI-S score was significantly higher in the study group than the control group ( P = 0.001) especially among the male groups between the age groups of <20, 20–29, and 30–39 years.…”
Section: Discussionsupporting
confidence: 85%
“…The mean Russell's Periodontal Index score amongst substance abusers was 3.68, whereas other studies by Angelillo et al [12], Shapiro et al [13], Picozzi et al [17], and Rosenstein [15] reported a mean Periodontal Index of 1.37, 2.2, 2.8–3.0, and 2.3, respectively. This difference may be explained by educational and sociodemographic background and ethnic and racial differences.…”
Section: Discussionmentioning
confidence: 79%
“…An increase in dental caries has been seen in heroin abusers [19]. This might be the result of their intense craving for sweets [22][23][24][25][26], or due to apparent xerostomia, anxiety regarding dental treatment [22], and poor oral hygiene. Also of importance to the dental professional is the increased incidence of periodontal disease, oral fungal infections [27], oral viral infections [28], and hyperpigmentation of the tongue [29].…”
Section: Discussionmentioning
confidence: 99%
“…Also of importance to the dental professional is the increased incidence of periodontal disease, oral fungal infections [27], oral viral infections [28], and hyperpigmentation of the tongue [29]. As the primary oral effect of heroin use is dental decay [26], the dentist must be aware of this and incorporate measures such as more frequent recall appointments and constant reinforcements of oral hygiene with the patient.…”
Section: Discussionmentioning
confidence: 99%